Sidelobe reduction based on spectrum reshaping in microwave imaging - Wang, HuaiJun; Su, Yi; Xu, HongBo; Zhu, YuTao (Science China. Information sciences, 2011)
Sidelobe artifacts are a common problem in image reconstruction from finite-extent Fourier data obtained by microwave imaging system. In order to enhance the image quality, sidelobe reduction must be implemented. Taking the sidelobe reduction in microwave imaging as the research subject, this paper presents Fourier imaging technique firstly. Then the point spread function is obtained through Fourier inversion of rectangular spectral support data and the changing effect of sidelobe direction due to reshaping spectral support is demonstrated. Spectrum reshaping makes that the sidelobes of two Fourier images do not overlap. Based on the idea of separating sidelobes from mainlobe, a nolve method that reduces sidelobe levels while maintaining the imaging resolution is proposed. The performance of this method is analyzed. Finally, the simulated and measured data of typical microwave imaging systems such as synthetic aperture radar {SAR）, inverse synthetic aperture radar （ISAR） and real aperture radar are used to demonstrate the validity of the proposed method.